The value of hematological inflammatory parameters in the differential diagnosis of testicular torsion and epididymorchitis - (:unkn) unknown (E-CENTURY PUBLISHING CORP, 2021)
Objective: Aim of this study is to investigate the effectiveness of mean platelet volume (MPV), neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) values, that can easily be obtained with complete blood count (CBC), in the diagnostic differentiation of testicular torsion and epididymorchitis. Method: Data of patients, who admitted to the urology or emergency departments, diagnosed with acute scrotum, between 20082017, were reviewed and retrospectively extracted. Basic characteristics (age,etc.) of patients and blood test results were retrieved. Inflammatory markers such as MPV, NLR and PLR were compared between groups. Result: After determining inclusion/exclusion criteria, a total of 111 patients were divided as testicular torsion, epididymorchitis and control group, including 37 patients each. Mean age of groups were 19.27 +/- 6.93, 26.27 +/- 6.23 and 23.24 +/- 8.49 years, respectively. Statistical significance was found in epididymorchitis and testicular torsion groups compared to the control group according to NLR (P<0.01). PLR showed a statistically significant relationship only with the epididymorchitis group and control group (P=0.46). However, according to MPV values, no statistically significance was found between the groups. Additionally, ROC analyse was performed to evaluate predictive cut-off values of NLR and PLR for the diagnostic differentiation of both groups. Conclusion: Inflammatory markers, obtained from routinely performed low-cost CBC, might be used as adjuvant parameters to differentiate acute scrotal pathologies like testicular torsion and epididymorchitis.
Keywords: Epididymorchitis; lymphocyte; neutrophil; platelet; testicular torsion; MEAN PLATELET VOLUME; LYMPHOCYTE RATIO; PROGNOSTIC VALUE; NEUTROPHIL; MARKER